Adsorption study of mango peel activated carbon as iron removal for batik waste industry - Agung Nugroho; Nur Layli Amanah; Revo Gilang Firdaus (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2022)
A B S T R A C TMango peel waste which has a carbon functional group was converted to activated carbon. The as-synthesized activated carbon (AC) was then utilized as an adsorbent for batik waste which contains heavy metal substances such as Fe2+. The purpose of this study was to determine the optimum process variation in absorbing heavy metal ion Fe contained in batik waste. Four variation methods of activated carbon synthesis were explored to determine the most suitable method of AC synthesis. The results showed that the sample synthesized using a combination physical-chemical-physical process was the best process variation resulting in percentage removal of Fe2+ of 84.81%. FTIR showed that the functional groups in mango peel were visible for all variations of the process, namely hydroxyl (-OH) derived from cellulose and hemicellulose and carboxyl (-COOH) derived from pectin. The adsorption study showed that the most suitable isotherm for all process variations was Langmuir with an R2 value of 0.9999 for the MPAC-4 sample. The adsorption mechanism is physisorption with a value of E < 8 kJ/mol based on the D-R isotherm and has the largest adsorption capacity of Qmax 8.2 mg/g.Keywords: batik waste; adsorption; activated carbon; iron waste; mango peelABSTRAKLimbah kulit mangga yang memiliki gugus fungsi karbon dapat dikonversi menjadi karbon aktif. Karbon aktif hasil sintesis (AC) tersebut selanjutnya dimanfaatkan sebagai adsorben limbah batik yang mengandung zat logam berat seperti Fe2+. Tujuan dari penelitian ini adalah untuk mengetahui variasi proses optimum dalam menyerap ion logam berat Fe yang terkandung dalam limbah batik. Terdapat 4 variasi metode sintesis karbon aktif yang diteliti untuk menentukan metode sintesis AC yang paling cocok. Hasil penelitian menunjukkan bahwa sampel yang disintesis menggunakan kombinasi proses fisika-kimia-fisika merupakan variasi proses terbaik dengan persentase penyisihan Fe2+ sebesar 84,81%. Analisis FTIR menunjukkan bahwa gugus fungsi pada kulit mangga terlihat untuk semua variasi proses, yaitu hidroksil (-OH) yang berasal dari selulosa dan hemiselulosa dan karboksil (-COOH) yang berasal dari pektin. Studi adsorpsi menunjukkan bahwa isoterm yang paling cocok untuk semua variasi proses adalah Langmuir dengan nilai R2 = 0,9999 untuk sampel MPAC-4. Mekanisme adsorpsi adalah fisisorpsi dengan nilai E < 8 kJ/mol berdasarkan isoterm DR dan memiliki kapasitas adsorpsi terbesar Qmax 8,2 mg/g.Kata kunci: limbah batik; adsorpsi; karbon aktif; limbah besi; kulit mangga